Digitalization Training of Learning Tools Based on Deep Learning to Improve the Quality of Mathematics Teaching for Teachers in the MGMP of Junior High Schools in Kabupaten 50 Kota - Yerizon - (Pelita Eksakta, 2026)
This Community Service Program (PkM) aims to enhance the competence of mathematics teachers in designing digital learning materials based on deep learning through the Integrated Study Program and Nagari Program (PIPN). The activity involved 47 teachers from 40 junior high schools in Kabupaten 50 Kota and was carried out through workshops, independent work, group collaboration, and presentation sessions. The materials delivered included the development of digital teaching modules, interactive media using ClassPoint and Canva, digital assessments through Quizizz and Wordwall, as well as the use of Heyzine as a platform for publishing teaching materials. Evaluation results showed a significant improvement in teachers’ abilities, indicated by an increase in the “moderate” competence category from 29% to 68% and a decrease in the “low” category from 66% to 21%. This program proved effective in improving mathematics teachers’ digital literacy and strengthening the implementation of deep learning–based instruction in schools.